Wisdom Local Mine Around Village After Pray Day Raya Eid Fitri According to Jean Baudrilla’s Perspective - Putri, Septia Eka; Umilia, Hafzah; Febriani, Rini; Ramadhani, Ira; Nugraha, Reza; Maksum, Mahatir; Fillta, Nadya (GIC Proceeding, 2024)
The objective of this research is to elucidate the Mining tradition (Seeking THR) prevalent in the vicinity subsequent to the Idul Fitri prayers, and to expound upon the inherent local wisdom values within said tradition. Employing a qualitative approach, this study seeks to delineate the form of mining traditions and explicate the local wisdom values they embody. Additionally, it endeavors to identify the supporting factors and elucidate the essence of local mining wisdom (pursuing THR). The theoretical framework utilized for analysis is Jean Baudrillard’s theory. Methodologically, this research employs interactive analysis techniques encompassing data collection, reduction, presentation, and drawing conclusions.